Rivero-Carvallo Sign in Bioprosthetic Tricuspid Valve Stenosis - Kazuhito Hirata, MD; Nobuhito Yagi, MD; Minoru Wake, MD (JACC: Case Reports, 2023)
In a case with bioprosthetic tricuspid stenosis, simultaneous phonocardiogram and Doppler recordings revealed that the louder diastolic rumble in inspiration (Rivero-Carvallo sign) is related to increased tricuspid gradient caused by less prominent decrease of right atrial pressure compared with that of the right ventricle in inspiration caused by tricuspid stenosis. (Level of Difficulty: Intermediate.)